THE DEVELOPMENT OF ORAL SPEECH WHEN WORKING WITH A SPECIAL TEXT (American Journal of Research in Humanities and Social Sciences, 2023)
This article discusses the features of language and speech, as well as the development of oral and written speech of students through working with text. The article presents tasks and examples that encourage students to understand the grammar of the Uzbek language by working with texts orally and in writing, as well as aspects that should be paid attention to when compiling them.